2021
DOI: 10.14740/cr1276
|View full text |Cite
|
Sign up to set email alerts
|

Corrected QT Interval Prolongation, Elevated Troponin, and Mortality in Hospitalized COVID-19 Patients

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has risen to the level of a global pandemic. Growing evidence has proven the cardiac involvement in SARS-CoV-2 infection. This study aims to evaluate the ability of cardiovascular complications determined by elevated troponin and electrocardiogram findings (e.g., corrected QT interval (QTc)) in predicting the severity of SARS-CoV-2 infection among hospitalized patients.Methods: This is a retrospective review of medical records o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Além disso, Al-Zakhari et al analisaram retrospectivamente 339 pacientes e demonstraram que o intervalo QTc prolongado tem uma relação independente e estatisticamente significativa com a mortalidade em pacientes hospitalizados por SARS-COV-2 (r = -0,173, p<0,05, 95% IC: -0,277, -0,064). 25 …”
Section: Discussionunclassified
See 1 more Smart Citation
“…Além disso, Al-Zakhari et al analisaram retrospectivamente 339 pacientes e demonstraram que o intervalo QTc prolongado tem uma relação independente e estatisticamente significativa com a mortalidade em pacientes hospitalizados por SARS-COV-2 (r = -0,173, p<0,05, 95% IC: -0,277, -0,064). 25 …”
Section: Discussionunclassified
“…Also, Al-Zakhari et al retrospectively analyzed 339 patients and demonstrated that the prolonged QTc interval has an independent and statistically significant relationship with mortality in patients hospitalized for SARS-COV-2 (r = -0.173, p < 0.05, 95% CI: -0.277, -0.064). 25 …”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum troponin levels on admission statistically correlated with mortality in COVID-19 patients ( Al-Zakhari et al, 2021 ). In a retrospective cohort analysis, cTnI was significantly elevated in 54 subjects who died compared with 137 survivors (median [IQR] cTnI 22 [5.6–83.1] ng/L vs. 3 [1.1–5.5] ng/L, p ≤ 0.0001) ( Zhou et al, 2020 ).…”
Section: Diagnostic Value Of Troponin In Covid-19mentioning
confidence: 99%
“…Evidence of COVID-19-associated increases in circulating cardiac Troponin T (cTnT) and cardiac Troponin I (cTnI) above the 99th percentile reference limit is emerging in the literature (Wang et al, 2020a;Liu et al, 2020d;Ruan et al, 2020). Elevated serum troponin levels on admission statistically correlated with mortality in COVID-19 patients (Al-Zakhari et al, 2021). In a retrospective cohort analysis, cTnI was significantly elevated in 54 subjects who died compared with 137 survivors (median [IQR] cTnI 22 [5.6-83.1] ng/L vs. 3 [1.1-5.5] ng/L, p ≤ 0.0001) (Zhou et al, 2020).…”
Section: Troponin Structure and Functionmentioning
confidence: 99%